Work Experience And Compensation Analysis On Employee Performance PT Widya Indria Sari Sibolga - Ella Martha Andriani; Rizal Ahmad (Yayasan Multidimensi Kreatif, 2024)
The research analysis aims to find out whether work experience and compensation influence employee performance. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This research uses multiple linear regression analysis. The sample in this study was 80 respondents. Primary data collection uses a questionnaire. The results of the research show that work experience partially has a positive and significant effect on employee performance at PT Widya Indria Sari Sibolga. Compensation partially has a positive and significant effect on employees at PT Widya Indria Sari Sibolga Work experience and compensation simultaneously have a positive and significant effect on employee performance at PT Widya Indria Sari Sibolga.